Removal of Methylene Blue from Wastewater by Adsorption onto ZnCl2 Activated Corn Husk Carbon Equilibrium Studies - Maryam Khodaie; Nahid Ghasemi; Babak Moradi; Mohsen Rahimi (Journal of Chemistry)
The removal of methylene blue by activated carbon of corn husk by ZnCl2 activation () was investigated in the present study. Adsorption studies were performed by batch experiments. The effect of pH, initial dye concentration, adsorbent dose, the particle size of , agitation speed, temperature, and contact time was explored. The equilibrium adsorption data were analyzed using two widely applied isotherms: Langmuir, Freundlich. Best fits were found to be Freundlich isotherm. Langmuir adsorption capacity () in 298, 308, and 318 K is 462.96, 546.45, and 662.25 mgg−1. The amount of indicates that has a favorable adsorption. Maximum MB removal was observed at pH 4.0. The results indicate that is an efficient adsorbent for removing dye from wastewater.